Value for money in self‐regulated procedural simulation. (13th February 2019) - Lafleur, Alexandre; Demchuk, Gabriel; Tremblay, Marie‐Laurence; Simard, Caroline; Rivière, Étienne
Summary: Background: In self‐regulated procedural simulation, learners practise on many simulators (e.g. paracentesis), self‐regulating their choice of simulators, time and goals. Current needs assessments cannot predict the number of simulators needed to plan cost‐effective self‐regulated simulation. Knowing the ratios of simulators and participants would allow for better‐informed purchase decisions to be made. Methods: We designed 90‐minute sessions of self‐regulated procedural simulation for internal medicine residents. In Phase 1, 51 participants (8.5 per group) could use 22 simulators (US69 925): ultrasound‐guided central ( n = 6) and peripheral ( n = 2) venous catheterisation; thoracocentesis ( n = 2); paracentesis ( n = 2); lumbar puncture ( n = 6); and arthrocentesis ( n = 4). We calculated minimal numbers of simulators based on the time that participants used each simulator in order to design a resource‐effective Phase 2, with 24 participants (with 12 per group) using 14 simulators (US48 720) to meet their needs. Results: Calculated from time of use (83 minutes in total), the optimal ratios of simulators expressed for 10 participants were 9.2: 3.7 for jugular and subclavian venous catheterisation (33 minutes); 1.5 for thoracocentesis (13 minutes), 1.0 for femoral venous catheterisation (9 minutes), 1.0 for lumbar puncture (9 minutes), 0.8 for peripheral venous catheterisation (8 minutes), 0.7 for paracentesis (6 minutes) and 0.5 for arthrocentesis (5 minutes). In Phase 2, the usage rate of simulators increased from 35.5% to 76.6%, maintaining the total time of use at 80.4 minutes. Conclusions: We present a replicable method for the cost‐effective planning of self‐regulated simulation by measuring the use of simulators. Expressed as ratios of simulators per participant, this information can support purchase decisions and be shared with similar programmes.